Study on Fabrication and Material Properties of Al Doped ZnO Films Prepared by Atmospheric Atomic Layer Deposition - Trinh, Quang Thong; Nguyen, Thi Huong Lan; Trieu, Viet Phuong; Judith L., MacManus-Driscol (JST: Engineering And Technology For Sustainable Development, 2021)
This paper presents the study on aluminium-doped zinc oxide (AZO) films prepared by atmospheric atomic layer deposition (AALD) using Diethylzinc (DEZ), Zn(C2H5)2, and Trimethylaluminum (TMA), Al(CH3)3 as precursors. The optimal condition for doping was investigated by changing in DEZ/TMA ratio. The crystal structure of fabricated thin films shows the hexagonal wurtzite structure with the orientation along the c-axis. The influence of heat treatment on the grain size, carrier type and concentration of post-fabricated films deposited on the different substrates which are borosilicate glass and sapphire was also analysed. The Hall measurement to determine the carrier type and resistivity at room temperature to 400°C was performed. The measurement results show that as-deposited samples behave as alloy-like property with p-type carriers and high resistivity. However, they turned into n-type nature as expected with the increase in carrier concentration and consequently the marked decrease in electrical resistance when annealed at the higher temperatures that are at 500°C and 900°C (i.e., 773 K and 1173 K). In general, the obtained films with optimized experimental conditions of as- and post-fabrication can be used for thermoelectric applications.